Perceptions across scales of governance and the Indonesian peatland fires - Carmenta, R.; Zabala, A.; Daeli, W.; Phelps, J. (Elsevier, 2017)
Across leading environmental challenges—fire management, climate change, deforestation – there is growing awareness of the need to better account for diverse stakeholder perceptions across complex, multi-level governance arrangements. Perceptions often condition behavior, compliance and engagement in ways that impact environmental outcomes. We illustrate the importance of, and approaches to, examining perceptions across scales of governance (e.g. international, national, local) and sectors (e.g. civil society, government, corporate) through the example of Indonesian peatland fires. Peatlands are crucial global carbon stocks threatened by land use change and fire and subject to a range of policy interventions that affect many different stakeholder groups. Peatland drainage and conversion to plantation agriculture has been associated with severe, uncontrolled peat fires that present significant climate, public health and economic risks. Peatland fire management has become a domestic and international priority, spurring intensely contentious debates, policies and legal proceedings. Previous fire management interventions (FMI) are numerous yet have suffered widespread implementation failures. Against this backdrop, our manuscript provides a thematically and methodologically novel analysis of how diverse stakeholders, from local farmers to international policy makers, perceive peatland fires in terms of, i) how they prioritize the associated benefits and burdens, and ii) the perceived effectiveness of FMI. We adopt an innovative application of Q method to provide needed insights that serve to quantify the areas of contention and consensus that exist among the stakeholders and their multi-dimensional perspectives. We show that many of the contemporary FMI were perceived as among the most effective interventions overall, but were also the most controversial between groups. Clear consensus areas were related to the shared concerns for the local health impacts and the potential of government support for fire-free alternatives as a solution pathway. Improved understanding of stakeholder perceptions has potential to: give voice to marginalized communities; enable transparent mediation of diverse priorities; inform public education campaigns, and shape future policy and governance arrangements.